THE ROLE OF QUR’ANIC TEACHER TO IMPROVING SANTRI'S QUR’ANIC READING ABILITY AT TPQ AL-MUHAJIRIN POLIN VILLAGE, SIWALALAT DISTRICT, EAST SERAM REGENCY - Juniati Ipa Ipa; Yusuf Abdurrahman Luhuliha; La Adu Adu (IAIN Ambon, 2022)
The background of this research is that non-formal education such as TPQ is very important and helps instill a love for the Al-Quran in children and this must be encouraged from an early age. Because many teenagers do not know how to read the Koran, there are also those who read quickly without paying attention to reading rules. This is a portrait to be reckoned with by teachers and parents alike. Qualitative research methods are used in this research. Data collection techniques in the form of observation, question and answer and communication as well as data analysis techniques in the form of reduction steps, data presentation and drawing conclusions. The results of the study show that the role of TPQ Al-Muhajirin educators in improving students' scientific literacy skills in Polin Village is as follows: (a) their role as teachers, where teachers teach students to understand the Qur'an and pronunciation, (b) as demonstrators , where the teacher presents pronunciation material using practical methods and demonstrations, (c) as a motivator, the teacher enthusiastically motivates and recommends students (d) the facilitator, where the teacher provides facilities to make it easier for the teacher to convey the memorized material being taught (e) evaluator, where the teacher conducts an assessment to determine the level of achievement achieved after participating in learning activities (1) Supporting factors: high student interest, patience and sincerity of the teacher and infrastructure (2) inhibiting factors: lack of student discipline, differences in intelligence levels and unfavorable environmental conditions.